The effect of word of mouth and brand image on customer loyalty with customer satisfaction as an intervening variable - Dwi Gemina; Sudarijati Sudarijati; Annisa Suci Nur Azizah (Universitas Nusa Cendana, 2026)
This study examines the influence of word of mouth and brand image on customer loyalty among users of Yongki Komaladi flat shoes in Bogor Regency, with customer satisfaction serving as an intervening variable. In the increasingly competitive fashion and footwear industry, understanding the factors that foster customer loyalty is essential for maintaining long-term business sustainability and competitive advantage. Employing a quantitative research design, data were collected through questionnaires administered to 100 consumers selected using purposive sampling, with respondents required to be at least 17 years old and to have purchased Yongki Komaladi flat shoes on at least two occasions. Path analysis was used to examine both direct and indirect relationships among the variables. The findings reveal that word of mouth and brand image each exert positive and significant influences on customer satisfaction and customer loyalty. Customer satisfaction was also found to have a strong positive effect on loyalty, highlighting its central role in strengthening long-term consumer relationships. Furthermore, customer satisfaction successfully mediates the relationships between word of mouth and customer loyalty as well as between brand image and customer loyalty, indicating that favorable consumer recommendations and a strong brand image enhance loyalty by first increasing customer satisfaction. These findings underscore the importance of maintaining a positive brand reputation, encouraging customer advocacy, and delivering satisfying consumer experiences to strengthen loyalty within the fashion retail sector. Keywords: Word Of Mouth; Brand Image; Customer Loyalty; Customer Satisfaction